Valsalva Maneuver For The Early Management Of Supra-Ventricular Tachycardia In Emergency Department Settings: Scoping Review - Izzati Adha Pratitis; Inggried Angelica Valentina Wiliyams Peni; Kurhayati Kurhayati; Ayu Prawesti Priambodo (Universitas Muhammadiyah Semarang, 2026)
Supraventricular tachycardia (SVT) is a common arrhythmia, and early management is crucial to prevent complications. The Valsalva maneuver, a non-invasive technique, has proven effective as a first-line therapy, with modifications enhancing its success. This scoping review explores evidence on the use of the Valsalva maneuver in managing SVT in emergency and pre-hospital settings, with a search in Scopus and PubMed using relevant keywords. Data were extracted independently from 16 articles that met inclusion criteria. The modified Valsalva maneuver significantly improves the success rate of converting SVT to sinus rhythm, with minimal side effects. Postural modifications were more effective than the standard maneuver and reduced reliance on pharmacological treatments. The modified Valsalva maneuver is effective, safe, and cost-efficient in managing SVT. However, its implementation requires more standardized protocols and better training for healthcare professionals.